2013
DOI: 10.1021/jp408239h
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Metal Interactions with the Prion Protein: EXAFS Analysis and Structure Calculations of Copper Binding to a Single Octarepeat from the Prion Protein

Abstract: Copper coordination to the prion protein (PrP) has garnered considerable interest for almost 20 years, due in part to the possibility that this interaction may be part of the normal function of PrP. The most characterized form of copper binding to PrP has been Cu2+ interaction with the conserved tandem repeats in the N-terminal domain of PrP, termed the octarepeats, with many studies focusing on single and multiple repeats of PHGGGWGQ. Extended X-ray absorption fine structure (EXAFS) spectroscopy has been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Besides anions, cations dissolved in aqueous solution have proved to be the key to the changes in water properties [ 1 , 2 ]. In addition, metal ions can also interact with a variety of biomolecules, such as protein [ 3 ] and DNA [ 4 ], and further lead to their structural changes to different extents. In this process, metal ions may bind directly with the functional groups on biomolecules [ 3 , 5 ] but may also indirectly force biomolecules to degenerate by alternating the water structure surrounding the biomolecules [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides anions, cations dissolved in aqueous solution have proved to be the key to the changes in water properties [ 1 , 2 ]. In addition, metal ions can also interact with a variety of biomolecules, such as protein [ 3 ] and DNA [ 4 ], and further lead to their structural changes to different extents. In this process, metal ions may bind directly with the functional groups on biomolecules [ 3 , 5 ] but may also indirectly force biomolecules to degenerate by alternating the water structure surrounding the biomolecules [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…EXAFS spectroscopy is a powerful technique for obtaining structural and chemical information about metal binding to a protein of interest, providing accurate bond length measurements within 5 Å or less. Several groups have analyzed by EXAFS copper coordination bound to recombinant PrP in the OR 29 and non-OR regions 30 31 . In a previous EXAFS study we found that at pH 5.5 Cu(II) and Cu(I) bound to wild-type (WT) are specifically coordinated by the N δ -atom in the imidazole ring of two His residues (H96 and H111), by deprotonated amide nitrogens from adjacent residues ( e.g.…”
mentioning
confidence: 99%
“…253 The role of metal ions in these conformational changes and in the onset of prion disease is still a matter of debate but more and more experimental evidence support the role of Cu(II) ions in these processes. 257 The results of theoretical calculations combined with experimental UV-visible studies on the Cu(II) complexes of a similar prion fragment were also reported. One of them describes the solution equilibria and structures of the Cu(II) complexes of the N-terminal peptide fragments of prion protein.…”
Section: Metal Complexes Of Peptide Fragments Of Prion Proteinmentioning
confidence: 90%